Strategi Pembelajaran Bipa Dengan Pendekatan Konstruktivisme Berbasis Kebudayaan Lokal - Istiana, Berti; Nurlina, Laily (Shofanah Media Berkah, 2023)
The purpose of this research is [1] to provide a description of the constructivist approach for BIPA students, [2] to explain the role of local culture as a source of learning materials for BIPA students, and [3] as a basis for implementing a constructivist approach based on local culture in BIPA learning. The method used in this research is a library study using books and journal articles as data sources. Data collection was carried out by accessing sources to deepen understanding of BIPA learning strategies, constructivist approaches and local culture. Data analysis was carried out through comparative methods and validation of validity using source triangulation. The research results concluded that applying a constructivist approach can enrich BIPA learning vocabulary. Apart from that, introduction to local culture can make a significant contribution, creating a more enjoyable classroom atmosphere and increasing interest in learning so that differentiated learning is formed.